SEISMIC-GEOLOGICAL ANALYSIS OF THE SOUTH CASPIAN MEGA DEPRESSION EVOLUTIONARY DEVELOPMENT TO IDENTIFY HYDROCARBON ACCUMULATIONS - ПОГОРЄЛОВА, Єлена; АБДУЛЛА-ЗАДЕ, Мурад; АБІЛГАСАНОВА, Лала; ШІХМАММАДОВА, Теллі (Київський національний університет імені Тараса Шевченка, 2024)
Background. The South Caspian Mega Depression (SCMD) is a territory limited in the west by the Dziruly massif, in the east by the Western Turkmenian Depression (inclusive), in the north by the mountain structures of the Greater Caucasus, Greater Balkhan and in the south restricted by the Lesser Caucasus, Talysh and Albours (including the aquatic area of the Southern Caspian) which in turn is related to the South Caspian oil and gas mega-basin. In the geodynamic model, the SCMD represents the Caucasian segment of the Alpine-Himalayan folded belt (its intermountain part) with elements of the active stage of development inherent in this area – earthquakes, sea level changes, mud volcanism, etc.    Methods. This article examines the history of the development of SCMD based on data from geophysics, drilling, volcanology, geodynamics in order to identify accumulations of hydrocarbons. Seismogeological sections presented throughout the study area explain the complex geological structure and geodynamics, starting from the baikalian tectonic genesis and up to the present time. The clear boundaries of sedimentary basins and the island arcs surrounding them, which controlled lithology and stratigraphy, make it possible to predict probable petroleum source rock and oil and gas-producing rocks.  Results. The construction of structural multi-temporal sediment surfaces in the Petrel program made it possible to trace the geological development of a certain segment (the South Caspian Aquatic Basin) of the studied territory, to clarify the influence of both long-lived deep and short-term local faults on the petrological composition of sediments and their thickness to determine the contours of possible objects of oil and gas formation.  Conclusions. The approximation of the outlined oil and gas source rocks (by PetroMod modeling) stratigraphic units on the territory of Western Turkmenistan to the western part of the SCMD assumes the allocation of hydrocarbon sources in deep-submerged rocks in the rest of the territory. The combination of seismometry and volcanology data makes it possible not only to outline geological bodies on seismic profiles, but also to determine their density composition and chemistry by the speed of propagation of seismic waves.

Вступ. Південнокаспійський мегапрогиб (ПКМП) – це територія, обмежена на заході масивом Дзирули, на сході Західнотуркменською западиною (включно), на півночі гірськими структурами Великого Кавказу, Великого Балхану, а на півдні – Малим Кавказом, Талишем і Албуром (включаючи акваторію Південного Каспію), яка, у свою чергу, пов'язана з Південнокаспійським нафтогазоносним мегабасейном. У геодинамічній моделі ПКМП являє собою кавказький сегмент Альпійсько-Гімалайського складчастого поясу (його міжгірську частину) з елементами активної стадії розвитку, притаманними цій території, а саме – землетрусами, змінами рівня моря, грязьовим вулканізмом тощо.    Методи. У статті розглянуто історію розвитку ДДЗ на основі даних геофізики, буріння, вулканології, геодинаміки з метою виявлення скупчень вуглеводнів. Сейсмогеологічні розрізи, представлені по всій досліджуваній території, пояснюють складну геологічну будову та геодинаміку, починаючи з байкальського тектонічного генезису і до сьогодення. Чіткі межі осадових басейнів та острівних дуг, що їх оточують, які контролювали літологію та стратиграфію, дають змогу прогнозувати ймовірні нафтогазоносні та нафтогазопродуктивні породи.   Результати. Побудова структурних різночасових поверхонь відкладів у програмі Petrel дозволила простежити геологічний розвиток певного сегмента (Південнокаспійської западини) досліджуваної території, з'ясувати вплив як довготривалих глибинних, так і короткочасних локальних розломів на петрологічний склад відкладів та їх потужність, визначити контури можливих об'єктів нафтогазоутворення.  Висновки. Наближення виділених (за моделюванням PetroMod) стратиграфічних одиниць нафтогазоносних порід на території Західного Туркменістану до західної частини ДДЗ передбачає виділення джерел вуглеводнів у глибокозанурених породах на решті території. Поєднання даних сейсмометрії та вулканології дає змогу не тільки окреслити геологічні тіла на сейсмічних профілях, але й визначити їхній густинний і хімічний склад за швидкістю поширення сейсмічних хвиль.
СЕЙСМОГЕОЛОГІЧНИЙ АНАЛІЗ ЕВОЛЮЦІЙНОГО РОЗВИТКУ ПІВДЕННОКАСПІЙСЬКОЇ МЕГАПРОГИНУ З МЕТОЮ ВИЯВЛЕННЯ СКУПЧЕНЬ ВУГЛЕВОДНІВ
Keywords: South Caspian Mega Depression; Greater Caucasus; Lesser Caucasus; Talysh; Alborz; geodynamic model; hydrocarbon sources; Південнокаспійський мегапрогиб; Великий Кавказ; Малий Кавказ; Талиш; Албурс; геодинамічна модель; джерела вуглеводнів